Neodymium-iron-boron magnetic powder, rare earth permanent magnet, method and application

By using amide substances and solid modifiers of pentaerythritol stearate in the airflow grinding process of neodymium iron boron magnetic powder, combined with the use of liquid modifiers, the problem of improving the fluidity of neodymium iron boron magnetic powder and the performance of rare earth permanent magnets is solved. Efficient magnetic performance improvement and production simplification are achieved.

CN119132775APending Publication Date: 2024-12-13BAOTOU RESEARCH INSTITUTE OF RARE EARTHS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411325161.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the fluidity of neodymium iron boron magnetic powder and the residual magnetic properties of rare earth permanent magnets, and traditional modifiers have problems such as poor anti-oxidation effect, volatile evaporation and high-temperature carbonization to form residual carbon.

Method used

The solid-state modifier is composed of amide substances and pentaerythritol stearate. It is mixed with the coarse powder of neodymium iron boron alloy through the airflow grinding process to reduce the resting angle and improve the flowability. At the same time, the liquid modifier is used to mix with neodymium iron boron magnetic powder. Sintering and aging treatment are performed to improve the residual magnetic and magnetic energy accumulation of rare earth permanent magnets.

Benefits of technology

It significantly improves the fluidity of neodymium iron boron magnetic powder and the residual magnetic and magnetic energy accumulation of rare earth permanent magnets, basically does not reduce coercive force, and simplifies the production process and extends the service life of the equipment.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses neodymium iron boron magnetic powder, a rare earth permanent magnet, a method and application. The invention discloses a method for improving fluidity of neodymium iron boron magnetic powder. The method comprises the following steps: 1) providing alloy coarse powder obtained by hydrogen decrepitation of an alloy melt-spinning sheet; (2) a solid modifier and the alloy coarse powder obtained in the step (1) are mixed and subjected to jet milling, and neodymium iron boron magnetic powder is obtained; wherein the mass of the solid modifier is 0.2-0.8 wt% of the mass of the alloy coarse powder; the solid modifier is composed of an amide substance and pentaerythritol stearate, and the mass of the amide substance accounts for 68-95 wt% of the mass of the solid modifier; the amide substance is selected from octadecanamide and / or oleamide; the repose angle of the obtained neodymium iron boron magnetic powder is smaller than or equal to 44.5 degrees. According to the method, the residual magnetism of the obtained rare earth permanent magnet can be further improved, and the coercive force of the rare earth permanent magnet is basically not reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to NdFeB magnetic powder, rare earth permanent magnet, method and application. Background Art

[0002] In today's rapidly developing technological era, high-end NdFeB magnets are the core materials for cutting-edge technology fields such as new energy vehicle drive motors and robot servo systems, and their importance is self-evident. NdFeB magnets provide powerful power support for modern industrial equipment with their excellent magnetic properties.

[0003] The performance of NdFeB magnets depends largely on the quality of their powders and processing technology. High-quality magnetic powder is the cornerstone of high-performance magnets. The preparation and service characteristics of high-performance sintered NdFeB magnets are inseparable from the grain boundary Nd-rich phase, and powder coating modification technology is an effective method to directly control the composition and distribution of the Nd-rich phase.

[0004] The particle size, distribution and fluidity of NdFeB powder almost directly determine the performance of the final magnet. With the continuous advancement of technology and the increasing requirements for magnet performance, the quality requirements for powder are becoming more and more stringent.

[0005] Traditional modifiers can no longer meet the needs of anti-oxidation treatment and fluidity improvement of ultrafine magnetic powder and high-abundance magnetic powder. They have the disadvantages of being volatile, having a strong odor, and having a poor coating effect, which seriously restricts the further improvement of magnet performance. At the same time, the residual carbon formed by high-temperature carbonization of the modifier interacts with the neodymium-rich phase at the grain boundary, which may also deteriorate the magnet performance.

[0006] CN114220622A discloses an antioxidant composition, a rare earth permanent magnet, a sintered magnet material, and a preparation method. The preparation method comprises smelting and coarsely crushing the components of the sintered magnet material except the antioxidant composition to obtain a coarse powder; then finely crushing the mixture of the coarse powder and 40% to 60% of the antioxidant composition to obtain a fine powder; then molding and sintering the mixture of the fine powder and the remaining antioxidant composition. The antioxidant composition comprises the following components: 30mas% to 60mas% of polyalphaolefin; 10mas% to 30mas% of butyl oleate; 1mas% to 20mas% of fatty acid methyl ester; and 10mas% to 40mas% of solvent oil. The amount of antioxidant composition used in this patent document is large, and the types of liquid organic substances are complex. It cannot be effectively adsorbed on the surface of magnetic powder in the air flow grinding and strong air flow environment, and the lubrication and anti-oxidation effects are limited. In addition, the maximum remanence of the magnets in its embodiments 1 to 6 is only 14.4 kGs, that is, the fluidity and antioxidant performance of its magnetic powder are insufficient. In addition, the antioxidant is difficult to remove, and the residual carbon impurities in the magnet after sintering will significantly deteriorate the diffusion performance. The remanence of the obtained rare earth permanent magnet is low, and the squareness of the magnet still needs to be improved.

[0007] CN115691924A discloses a method for preparing a NdFeB magnet, comprising the following steps: step 1, mixing neodymium, boron, copper, dysprosium and iron and performing vacuum melting to obtain a NdFeB magnet alloy; step 2, subjecting the NdFeB alloy to hydrogen crushing to obtain a NdFeB coarse powder, adding additives in a proportion of 0.05-0.1% of the mass of the NdFeB coarse powder, and mixing them uniformly to obtain a mixed powder, subjecting the mixed powder to a jet milling process to obtain a NdFeB fine powder, wherein the additive is a composition of glyceryl monostearate, tributyl borate and oleic acid mixed in a mass percentage of 40-50%: 20-30%: 20-40%; step 3, pressing the NdFeB fine powder into a green body, encapsulating the green body, and isostatically pressing the encapsulated green body to obtain an isostatic green body; step 4, vacuum sintering the isostatic green body to obtain a NdFeB magnet. The liquid modifier in the patent document is not easy to be stably adsorbed on the surface of the magnetic powder during the air flow milling stage, the magnetic powder has insufficient oxidation resistance and fluidity, the residual magnetism of the obtained NdFeB magnet is not significantly improved, and the squareness of the magnet still needs to be improved.

[0008] CN115331941A discloses a method for modifying high-fluidity sintered NdFeB magnetic powder and a NdFeB sintered body, the modification method comprising: step 1, using an inert gas to exhaust oxygen from the mixing chamber of a high-efficiency shearing mixer to make its oxygen content less than 50ppm; step 2, under the protection of an inert atmosphere, passing the sintered NdFeB magnetic powder through an atomized liquid modifier or a suspended solid modifier and adding it to the mixing chamber treated in step 1; step 3, using an efficient shearing mixer to shear and mix the sintered NdFeB magnetic powder, and during the mixing process, using a high-pressure inert gas spray device or a solidification device to add the remaining liquid modifier or solid modifier; step 4, after the mixing is completed, the powder is connected to a material tank protected by an inert gas to obtain modified sintered NdFeB magnetic powder. The angle of repose of the sintered NdFeB magnetic powder obtained in the patent document is still high, and the residual magnetism and squareness of the magnet are still low. Summary of the invention

[0009] In view of this, an object of the present invention is to provide a method for improving the fluidity of NdFeB magnetic powder, which method is beneficial to further reduce the repose angle of the obtained NdFeB magnetic powder, thereby improving its fluidity, and further beneficial to further improve the remanence of the obtained rare earth permanent magnet without substantially reducing its coercive force.

[0010] Another object of the present invention is to provide a NdFeB magnetic powder prepared according to the method as described above. Another object of the present invention is to provide a method for preparing a rare earth permanent magnet. The preparation method can further improve the remanence, magnetic energy product, and squareness of the obtained rare earth permanent magnet, and substantially does not reduce its coercive force. Another object of the present invention is to provide a rare earth permanent magnet prepared according to the preparation method as described above. Another object of the present invention is to provide an application of a solid modifier in improving the remanence of a rare earth permanent magnet.

[0011] The present invention adopts the following technical solutions to achieve the above-mentioned purpose.

[0012] In one aspect, the present invention provides a method for improving the fluidity of NdFeB magnetic powder, comprising the following steps:

[0013] 1) Providing alloy coarse powder obtained by hydrogen crushing of alloy strip pieces;

[0014] 2) mixing the solid modifier with the alloy coarse powder obtained in step 1) and jet milling to obtain NdFeB magnetic powder;

[0015] Wherein, the mass of the solid modifier is 0.2-0.8wt‰ of the mass of the alloy coarse powder;

[0016] Wherein, the solid modifier is composed of an amide substance and pentaerythritol stearate, the mass of the amide substance accounts for 68-95wt% of the mass of the solid modifier; the amide substance is selected from stearic acid amide and / or oleic acid amide;

[0017] The repose angle of the obtained NdFeB magnetic powder is less than or equal to 44.5°.

[0018] According to the method of the present invention, preferably, the amide substance is stearic acid amide.

[0019] On the other hand, the present invention also provides a NdFeB magnetic powder, which is prepared according to the method as described above.

[0020] In another aspect, the present invention further provides a method for preparing a rare earth permanent magnet, comprising the following steps:

[0021] (1) mixing the liquid modifier with the NdFeB magnetic powder as described above by a mixer to obtain mixed magnetic powder;

[0022] (2) pressing the mixed magnetic powder into a shape, and then sintering and aging the mixture to obtain the rare earth permanent magnet;

[0023] The liquid modifier comprises a high-level unsaturated fatty acid ester and an organic boron compound in a volume ratio of 1 to 4:1; the mass of the liquid modifier is 0.3 to 0.7 wt‰ of the mass of the NdFeB magnetic powder.

[0024] According to the method for preparing rare earth permanent magnets of the present invention, preferably, the liquid modifier is formed by a higher unsaturated fatty acid ester and an organic boron compound in a volume ratio of 1 to 4:1.

[0025] According to the method for preparing a rare earth permanent magnet of the present invention, preferably, the higher unsaturated fatty acid ester is selected from at least one of ethyl oleate, isooctyl oleate, methyl palmitate, methyl myristate, methyl stearate and methyl laurate; and the organic boron compound is selected from at least one of triisopropyl borate, tributyl borate and triethyl borate.

[0026] According to the method for preparing rare earth permanent magnets of the present invention, preferably, when the vacuum degree is less than or equal to 1.0×10 - 1 The green body obtained by pressing and forming is sintered at 1030-1155°C for 3-7h to obtain a sintered magnet A.

[0027] According to the method for preparing rare earth permanent magnets of the present invention, preferably, the aging treatment comprises keeping the sintered magnet A at 870-950°C for 0.5-5h to obtain magnet B; and keeping magnet B at 400-650°C for 1-5h to obtain the rare earth permanent magnet.

[0028] In another aspect, the present invention further provides a rare earth permanent magnet, which is prepared according to the preparation method as described above.

[0029] In another aspect, the present invention further provides an application of a solid modifier in improving the remanence of a rare earth permanent magnet, wherein the solid modifier is composed of an amide substance and pentaerythritol stearate, wherein the amide substance accounts for 68 to 95 wt % of the solid modifier; and the amide substance is selected from stearic acid amide and / or oleic acid amide; and the method comprises the following steps:

[0030] 1) Providing alloy coarse powder obtained by hydrogen crushing of alloy strip pieces;

[0031] 2) mixing the solid modifier with the alloy coarse powder obtained in step 1) and jet milling to obtain NdFeB magnetic powder;

[0032] Wherein, the mass of the solid modifier is 0.2 to 0.8 wt‰ of the mass of the alloy coarse powder.

[0033] The present invention can further reduce the repose angle of the obtained NdFeB magnetic powder by using a specific solid modifier in the airflow milling process, that is, further improve the fluidity of the obtained NdFeB magnetic powder, thereby being conducive to further improving the remanence of the obtained rare earth permanent magnet, and substantially not reducing or being able to improve the coercive force of the magnet. The preparation method of the present invention is conducive to further improving the remanence and squareness of the obtained rare earth permanent magnet, and is conducive to significantly improving its magnetic energy product, and substantially not reducing the coercive force of the obtained rare earth permanent magnet. In addition, the preparation method of the present invention can omit the isostatic pressing process and shorten the production time. DETAILED DESCRIPTION

[0034] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0035] The "remanent magnetism" mentioned in the present invention refers to the value of the magnetic flux density corresponding to the point where the magnetic field intensity is zero on the saturation hysteresis loop, usually denoted as Br, and the unit is Tesla (T) or Gauss (Gs). 1Gs = 0.0001T.

[0036] The "coercive force" mentioned in the present invention, also known as the intrinsic coercive force, refers to the magnetic field intensity when the magnetic field is monotonically reduced to zero and then increased in the opposite direction from the saturated magnetization state of the magnet, so that the magnetization intensity decreases to zero along the saturation hysteresis loop, usually denoted as H cj , the unit is Oersted (Oe) or Ampere / meter (A / m). 1Oe=79.6A / m. cj is the intrinsic coercivity at room temperature.

[0037] Compared with the prior art, the present invention can further reduce the repose angle of the obtained NdFeB magnetic powder by adopting a specific solid modifier, that is, further improve the fluidity of the obtained NdFeB magnetic powder, which is beneficial to further improve the remanence and squareness of the obtained rare earth permanent magnet, and is beneficial to significantly improve its magnetic energy product, and basically does not reduce the coercive force of the obtained rare earth permanent magnet.

[0038] <NdFeB magnetic powder and method>

[0039] The present invention provides a method for improving the fluidity of NdFeB magnetic powder, comprising the following steps: 1) providing alloy coarse powder obtained by hydrogen crushing of alloy stripping pieces; 2) mixing a solid modifier with the alloy coarse powder obtained in step 1) and performing jet milling to obtain NdFeB magnetic powder. In this way, the repose angle of the obtained NdFeB magnetic powder can be reduced and the fluidity of the obtained NdFeB magnetic powder can be improved on the basis of mainly utilizing existing equipment and not increasing equipment investment, and the remanence and squareness of the obtained rare earth permanent magnet can be further improved, and its magnetic energy product can be significantly improved, and its coercive force is basically not reduced.

[0040] In the present invention, the addition amount of the solid modifier is 0.2-0.8wt‰ of the mass of the alloy coarse powder, preferably 0.4-0.7wt‰, more preferably 0.4-0.6wt‰, for example, it can be 0.4wt‰, 0.46‰, 0.52‰, 0.56wt‰, 0.6wt‰.

[0041] In the present invention, the solid state modifier is composed of an amide substance and pentaerythritol stearate, wherein the mass of the amide substance accounts for 68 to 95 wt % of the mass of the solid state modifier, preferably 68.5 to 92.8 wt %, for example, 68.5 wt %, 75 wt %, 78.8 wt %, 92.8 wt %. The mass of pentaerythritol stearate accounts for 5 to 32 wt % of the mass of the solid state modifier. The amide substance is selected from stearic acid amide (C 18 H 37 NO) and / or oleamide (C 18 H 35 NO), preferably stearic acid amide.

[0042] The present invention finds that, compared with existing liquid modifiers and other solid modifiers, the solid modifier of the present invention with a specific composition is more conducive to improving the fluidity of NdFeB magnetic powder, thereby being more conducive to further improving the magnetic properties of the obtained rare earth permanent magnet.

[0043] In addition, compared with the existing liquid modifiers, the solid modifier of the specific composition of the present invention has a low probability of being carried away by the nitrogen gas flow in the air flow mill environment, and is not easy to volatilize in large quantities to cause trouble to the operation of the system, thereby solving problems such as equipment maintenance, reducing damage such as wear and tear on the air flow mill equipment body, and extending the service life of the equipment.

[0044] In the present invention, the alloy stripping sheet is obtained by vacuum melting a raw material alloy containing components of a rare earth permanent magnet.

[0045] The rare earth permanent magnet of the present invention is R2Fe 14 B-type compound is a rare earth sintered permanent magnet with a main phase. R is selected from at least one element of light rare earth elements, and must contain Nd. Light rare earth elements are lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm) and europium (Eu). The rare earth permanent magnet of the present invention may contain or not contain heavy rare earth elements. In certain embodiments, the rare earth permanent magnet of the present invention does not contain heavy rare earth elements. Wherein, the heavy rare earth elements are gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu) and yttrium (Y).

[0046] The rare earth element of the present invention can be selected from at least one of La, Ce, Nd, Pr, and Sm. According to one embodiment of the present invention, R is selected from at least one of Pr and Nd, and must contain Nd. According to a preferred embodiment of the present invention, R is Nd and Pr. In the present invention, B is boron.

[0047] In the present invention, the rare earth permanent magnet may contain M, where M is selected from one or more of Cu, Co, Al, Ga and Zr.

[0048] In some specific embodiments, the rare earth permanent magnet has the following specific composition: R, Fe, B, Cu, Co, Al, Ga, Zr and other inevitable impurities. Based on all the elements of the rare earth permanent magnet, the content of R is 29.0-33.0wt%, preferably 30.0-32.0wt%, and more preferably 30.0-31.0wt%. Based on all the elements of the rare earth permanent magnet, the content of Cu is 0.10-0.20wt%, preferably 0.11-0.16wt%, and more preferably 0.13-0.15wt%. The content of Co is 0.1-1.5wt%, preferably 0.2-1.0wt%, and more preferably 0.4-0.6wt%. The content of Al is 0.1-1.2wt%, preferably 0.2-1.0%, and more preferably 0.4-0.7wt%. Based on all the elements of the rare earth permanent magnet, the content of B is 0.88-0.93wt%, preferably 0.89-0.93wt%, and more preferably 0.91-0.92wt%. Based on all the elements of the rare earth permanent magnet, the content of Ga is 0.05-0.6wt%, preferably 0.1-0.5wt%, and more preferably 0.15-0.4wt%. Based on all the elements of the rare earth permanent magnet, the content of Zr is 0.05-0.55wt%, preferably 0.1-0.50wt%, and more preferably 0.20-0.45wt%. Fe is the balance.

[0049] According to one embodiment of the present invention, alloy strip sheets can be obtained by vacuum melting according to the following components (i.e., the components of the rare earth permanent magnet finally obtained): PrNd 30.0-33.0wt%, Cu 0.13-0.20wt%, Co 0.4-0.8wt%, Al 0.4-0.5wt%, Ga0.15-0.20wt%, Zr 0.23-0.45wt%, B 0.90-0.93wt%, and Fe as the balance.

[0050] Vacuum smelting can be carried out using those equipment and methods known in the art. The raw materials containing R, Fe, B, and M can be smelted to obtain alloy strip sheets. In the present invention, in order to prevent the raw materials and the alloy strip sheets obtained therefrom from being oxidized, the smelting is carried out in a vacuum or inert atmosphere. The vacuum smelting process preferably adopts a rapid solidification casting process. The rapid solidification casting is a raw material of the rare earth permanent magnet after smelting that is rapidly cooled and solidified, and is spun into an alloy strip sheet. The thickness of the alloy strip sheet can be 0.1 to 0.5 mm, preferably 0.2 to 0.4 mm.

[0051] According to a specific embodiment of the present invention, raw materials containing R, Fe, B, and M are placed in a vacuum medium-frequency rapid solidification induction furnace, evacuated to less than 1 Pa, filled with argon gas, heated and melted under the protection of argon gas to form alloy liquid, and then the alloy liquid is poured onto a rotating cooling copper roller to prepare an alloy strip sheet with a thickness of 0.1 to 1.5 mm. The temperature of the alloy liquid is controlled between 1400 and 1500°C.

[0052] In the hydrogen crushing process, the alloy strip flakes are crushed into alloy coarse powder by a hydrogen crushing process. The hydrogen crushing process includes the following steps: firstly, the alloy strip flakes absorb hydrogen, and the alloy strip flakes are crushed by the reaction between the alloy strip flakes and hydrogen to induce the volume expansion of the alloy flake lattice, and then heated to dehydrogenate to obtain alloy coarse powder. According to a preferred embodiment of the present invention, the hydrogen crushing process of the present invention is preferably carried out in a hydrogen crushing furnace. The hydrogen pressure used during crushing can be 0.02 to 0.2 MPa, preferably 0.05 to 0.15 MPa. The vacuum dehydrogenation temperature can be 400 to 600 ° C. The average particle size D of the alloy coarse powder obtained by the hydrogen crushing process 50 The thickness may be 45 to 400 μm, preferably 350 μm or less, and more preferably 45 to 325 μm.

[0053] The airflow mill can adopt those known in the art. The airflow mill process is to use airflow to accelerate the alloy coarse powder and then collide with each other to break it. The airflow can be a nitrogen flow, preferably a high-purity nitrogen flow. The N2 content in the high-purity nitrogen flow can be above 99.0wt%, preferably above 99.9wt%. The pressure of the airflow can be 0.1-2.0MPa, preferably 0.5-1.0MPa, and more preferably 0.6-0.7MPa. No special oxygen is added during the airflow mill, and the oxygen content is less than 20ppm.

[0054] The invention mixes a specific solid modifier with alloy coarse powder and then uses air flow mill to form NdFeB magnetic powder.

[0055] The repose angle of the NdFeB magnetic powder obtained by the present invention is less than or equal to 44.5°, and can reach 42.1°. The smaller the repose angle, the better the fluidity. The average diameter of the specific surface area of ​​the obtained NdFeB magnetic powder is 2.5 to 3.5 μm, preferably 2.7 to 3.0 μm, more preferably greater than or equal to 2.8 μm and less than 3.0 μm; its D 90 / D 10 The bulk density is 1.70-1.80 g / cm 3 , preferably 1.71 to 1.76 g / cm 3 ; Its tap density is 3.55~3.95g / cm 3 , preferably 3.60 to 3.90 g / cm 3 , more preferably 3.70 to 3.85 g / cm 3 Such NdFeB magnetic powder is beneficial to further improve the remanence of the obtained rare earth permanent magnet when preparing the rare earth permanent magnet, and substantially does not reduce its coercive force.

[0056] <Rare earth permanent magnet and preparation method>

[0057] The method for preparing the rare earth permanent magnet of the present invention comprises the following steps:

[0058] (1) mixing the liquid modifier with the NdFeB magnetic powder as described above by a mixer to obtain mixed magnetic powder;

[0059] (2) The mixed magnetic powder is pressed into a shape, and then sintered and aged to obtain the rare earth permanent magnet. This is conducive to obtaining a rare earth permanent magnet with stable magnetic properties. The following is a detailed description.

[0060] In step (1), the liquid modifier comprises a higher unsaturated fatty acid ester and an organic boron compound in a volume ratio of 1 to 4:1; preferably, the liquid modifier is composed of a higher unsaturated fatty acid ester and an organic boron compound in a volume ratio of 1 to 4:1, and more preferably, the liquid modifier is composed of a higher unsaturated fatty acid ester and an organic boron compound in a volume ratio of 1 to 1.2:1. The liquid modifier can act as a lubricant and an antioxidant.

[0061] In the present invention, the higher unsaturated fatty acid ester is selected from at least one of ethyl oleate, isooctyl oleate, methyl palmitate, methyl myristate, methyl stearate and methyl laurate, preferably selected from one of ethyl oleate, isooctyl oleate, methyl palmitate and methyl laurate. The organic boron compound is selected from at least one of triisopropyl borate, tributyl borate and triethyl borate, preferably selected from one of triisopropyl borate, tributyl borate and triethyl borate.

[0062] In the present invention, the mass of the liquid modifier is 0.3-0.7wt‰ of the mass of the NdFeB magnetic powder, preferably 0.4-0.65wt‰, more preferably 0.4-0.6wt‰, for example, 0.4wt‰, 0.53wt‰, 0.56wt‰, 0.6wt‰.

[0063] In the present invention, the liquid modifier and the NdFeB magnetic powder can be mixed by high-speed shear mixing. For example, the mixer used is a high-efficiency shear mixer, and the linear speed of the edge of the mixer blade can be 25-30 m / s. When mixing, low-speed premixing can be performed first, and then high-speed mixing can be performed. The total mixing time is 25-50 minutes, preferably 30-40 minutes. This is conducive to uniform mixing, and the NdFeB magnetic powder is evenly coated with the liquid modifier.

[0064] In step (2), during the pressing process, the mixed magnetic powder is pressed in a magnetic field, and the direction of the orientation magnetic field is perpendicular to the pressing direction of the mixed magnetic powder. There is no particular restriction on the strength of the orientation magnetic field, which can be determined according to actual needs. The magnetic field strength is greater than or equal to 1.5 T, preferably greater than or equal to 1.75 T, and more preferably greater than or equal to 2.0 T. The maximum pressure is maintained for 1 to 10 seconds, preferably 3 to 5 seconds, during the pressing process of the magnetic powder.

[0065] The density of the green compact after magnetic powder magnetic field orientation is 4.0~4.4g / cm 3 . After the orientation is formed once, the green compact is subjected to an isostatic pressing treatment to obtain a green body. In order to prevent the magnetic powder from being oxidized, the orientation pressing and the isostatic pressing treatment are carried out in a vacuum or inert atmosphere. This is conducive to maintaining a high remanence of the magnet. The present invention can also omit isostatic pressing, which can improve the yield rate of the pressed green compact, simplify the production process, and especially can well control the size specifications of the pressed magnet, avoiding the occurrence of adverse problems such as oil leakage and green compact deformation during isostatic pressing.

[0066] In the sintering process, the green body is sintered to obtain a sintered magnet A. This is conducive to maintaining a high remanence and coercive force of the obtained magnet. The sintering process is carried out in a vacuum sintering furnace.

[0067] The vacuum degree during sintering is less than or equal to 1.0×10 -1 Pa is preferably less than or equal to 1.0×10 -2 Pa. The sintering temperature may be 1030-1155°C, preferably 1040-1135°C, more preferably 1050-1100°C. The sintering time may be 3-7h, preferably 3-6h, more preferably 3-4h. This is beneficial to improve the remanence of the obtained rare earth permanent magnet and keep the coercive force unchanged.

[0068] In the present invention, after the sintering heat preservation is completed, the sintered magnet A can be obtained by blast cooling to room temperature.

[0069] In the present invention, the aging treatment is preferably carried out in a vacuum state, and the vacuum degree is less than 1.0×10 -1 Pa is preferably less than or equal to 1.0×10 -2 Pa.

[0070] In the present invention, the aging treatment includes a first-stage aging treatment and a second-stage aging treatment. The first-stage aging treatment includes: keeping the sintered magnet A at 870-950°C for 0.5-5h to obtain a magnet B. The temperature of the first-stage aging treatment can be 870-950°C, preferably 890-940°C, and more preferably 910-930°C. The time of the first-stage aging treatment can be 0.5-5h, preferably 0.5-3h, and more preferably 0.5-2h.

[0071] The second aging treatment comprises: keeping the magnet B at 400-650° C. for 1-5 hours to obtain the rare earth permanent magnet. The temperature of the second aging treatment can be 400-650° C., preferably 450-600° C., and more preferably 450-550° C. The time of the second aging treatment can be 1-5 hours, preferably 2-5 hours, and more preferably 3-4 hours.

[0072] After the second stage aging treatment is completed, the rare earth permanent magnet is obtained by rapidly cooling to room temperature.

[0073] The remanence of the rare earth permanent magnet obtained by the present invention is further improved, the squareness is improved, the magnetic energy product is significantly improved, and the coercive force is basically not reduced or even improved. The squareness Hk / Hcj of the obtained rare earth permanent magnet is greater than or equal to 99.7%. The oxygen element in the obtained rare earth permanent magnet is less than 500ppm, the carbon element is less than 800ppm, and the nitrogen element is less than 400ppm.

[0074] <Application>

[0075] The present invention also provides an application of a solid modifier in improving the remanence of a rare earth permanent magnet, wherein the solid modifier is composed of an amide substance and pentaerythritol stearate, wherein the amide substance accounts for 68 to 95 wt % of the solid modifier; and the amide substance is selected from stearic acid amide and / or oleic acid amide; and the method comprises the following steps:

[0076] 1) Providing alloy coarse powder obtained by hydrogen crushing of alloy strip pieces;

[0077] 2) mixing the solid modifier with the alloy coarse powder obtained in step 1) and jet milling to obtain NdFeB magnetic powder;

[0078] The mass of the solid modifier is 0.2-0.8 wt‰ of the mass of the alloy coarse powder. The repose angle of the obtained NdFeB magnetic powder is less than or equal to 44.5°.

[0079] The following steps may also be included:

[0080] 3) mixing the liquid modifier with the NdFeB magnetic powder as described above by using a mixer to obtain mixed magnetic powder;

[0081] 4) pressing the mixed magnetic powder into a shape, and then sintering and aging treatment to obtain the rare earth permanent magnet;

[0082] The liquid modifier comprises a high-level unsaturated fatty acid ester and an organic boron compound in a volume ratio of 1 to 4:1; the mass of the liquid modifier is 0.3 to 0.7 wt‰ of the mass of the NdFeB magnetic powder. The detailed description is referred to above and will not be expanded here.

[0083] The invention adopts a specific solid modifier, which is beneficial to reducing the repose angle of the obtained NdFeB magnetic powder, improving the fluidity of the NdFeB magnetic powder, and further improving the remanence of the obtained rare earth permanent magnet without substantially reducing its coercive force; and is also beneficial to further improving the squareness of the obtained rare earth permanent magnet, and significantly improving the magnetic energy product of the obtained rare earth permanent magnet.

[0084] <Test Method>

[0085] Determination of loose density: Place NdFeB magnetic powder into a funnel with a vibrating device and a screen, and vibrate it under set conditions; the powder mixed with gas is made to fall naturally from the funnel at a set height through vibration and fill a measuring cup of known capacity. The loose density of the powder is expressed by dividing the unit volume by the mass of the powder when loosely packed.

[0086] Determination of tap density: Apply a certain tapping action to the loosely packed NdFeB magnetic powder until the mass of the powder in the fixed volume container no longer increases; the tap density of the powder is expressed by dividing the mass of the powder in the tightly packed state by the unit volume.

[0087] Determination of the angle of repose: Place NdFeB magnetic powder into a funnel with a vibrating device and a screen, and vibrate under set conditions; through vibration, the powder mixed with gas naturally falls from the funnel to the horizontal receiving tray at a set height, and the vibration is stopped when the NdFeB magnetic powder fills the receiving tray for one circle. Measure the acute angle between the accumulation surface of the NdFeB magnetic powder and the horizontal plane of the receiving tray, which is the angle of repose.

[0088] Determination of the specific surface average diameter: also known as the Sauter mean diameter, abbreviated as SMD, expressed as D(3,2), which means the diameter of a sphere with the same surface area as the actual particles. The particle size distribution of NdFeB magnetic powder is tested at room temperature using a Synpatek laser particle size analyzer and calculated according to the standard method ASTM E 799.

[0089] Determination of magnetic properties: The magnetic properties of the sintered body and the sintered permanent magnet were measured at room temperature using a BH magnetometer to obtain the room temperature remanence Br and room temperature coercivity Hcj of the sintered body and the sintered permanent magnet.

[0090] Preparation Example 1-Preparation of NdFeB Magnetic Powder

[0091] NdFeB magnetic powder is prepared according to the following components: PrNd 30.0wt%, Cu 0.13wt%, Co 0.4wt%, Al0.5wt%, Ga 0.2wt%, Zr 0.23wt%, B 0.91wt%, Fe balance. The raw materials containing the above components are vacuum smelted to obtain alloy strip pieces, and the alloy strip pieces are hydrogen crushed to obtain alloy coarse powder with a particle size range of 45 to 325μm.

[0092] The solid modifier is added to the alloy coarse powder and mixed, and then the mixture is subjected to jet milling to obtain NdFeB magnetic powder. The solid modifier is composed of: stearic acid amide (C 18 H 37 NO) is 78.8wt%, and pentaerythritol stearate (PETS) is 21.2wt%. The addition amount of the above solid modifier is 0.46‰ of the mass of the alloy coarse powder.

[0093] The repose angle of the obtained NdFeB magnetic powder is 44.5°, the average specific surface diameter is 2.84μm, and D 90 / D 10 The diameter is 4.80, and the bulk density is 1.71g / cm 3 , tap density is 3.75g / cm 3 .

[0094] Example 1 - Preparation of rare earth permanent magnets

[0095] After adding a liquid modifier to the NdFeB magnetic powder obtained in Preparation Example 1, a high-efficiency shear mixer was used for shear mixing for 40 minutes to obtain a mixed magnetic powder. The liquid modifier is a mixture of ethyl oleate and tributyl borate mixed in equal volumes at a ratio of 1:1, and the amount of the liquid modifier added is 0.6‰ of the mass of the NdFeB magnetic powder. The liquid modifier has both lubricity and antioxidant properties.

[0096] The mixed magnetic powder is oriented, and the density of the compact after one-step orientation is 4.25g / cm 3 Then the green compact is subjected to isostatic pressing to form a compact, followed by vacuum sintering. When the vacuum degree reaches 10 -2 Pa, sintering was started, and the sintering temperature was 1055℃ for 5.5h. The vacuum degree reached 10 -3 ~10 -4Pa, after the heat preservation, the sintered magnet A was obtained by blast cooling to room temperature. The sintered magnet A was subjected to the first aging treatment at 910°C for 1 hour to obtain magnet B; the magnet B was subjected to the second aging treatment at 500°C for 3 hours, and after the heat preservation of the second aging treatment, it was quickly cooled to room temperature to obtain a rare earth permanent magnet. The results of the magnet performance test are shown in Table 1.

[0097] Comparative Example 1

[0098] The same as Example 1 except for the following differences: In this comparative example, the solid modifier used when the NdFeB magnetic powder is formed in the jet milling stage is zinc stearate. The properties of the obtained rare earth permanent magnet are shown in Table 1.

[0099] Table 1

[0100] serial number Br / kGs HkDJ <![CDATA[BH max / MGOe]]> Hk / Hcj / % Example 1 14.52 16.52 50.75 99.7 Comparative Example 1 14.40 14.80 49.65 99.1

[0101] Preparation Example 2-Preparation of NdFeB Magnetic Powder

[0102] NdFeB magnetic powder is prepared according to the following components: PrNd 30.0wt%, Cu 0.13wt%, Co 0.4wt%, Al0.5wt%, Ga 0.2wt%, Zr 0.23wt%, B 0.91wt%, Fe balance. The raw materials containing the above components are vacuum smelted to obtain alloy strip pieces, and the alloy strip pieces are hydrogen crushed to obtain alloy coarse powder with a particle size range of 45 to 325μm.

[0103] The solid modifier is added to the alloy coarse powder and mixed, and then the mixture is subjected to jet milling to obtain NdFeB magnetic powder. The solid modifier is composed of: stearic acid amide (C 18 H 37 NO) is 92.8wt%, and pentaerythritol stearate (PETS) is 7.2wt%. The addition amount of the above solid modifier is 0.56‰ of the mass of the alloy coarse powder.

[0104] The repose angle of the obtained NdFeB magnetic powder is 44.0°, the average specific surface diameter is 2.92μm, and D 90 / D 10 The thickness is 4.45, and the bulk density is 1.76g / cm 3 , tap density is 3.82g / cm 3 .

[0105] Example 2 - Preparation of rare earth permanent magnets

[0106] After adding a liquid modifier to the NdFeB magnetic powder obtained in Preparation Example 2, a high-efficiency shear mixer was used for shear mixing for 40 minutes to obtain a mixed magnetic powder. The liquid modifier is a mixture of isooctyl oleate and triisopropyl borate mixed in equal volumes in a ratio of 1:1, and the amount of the liquid modifier added is 0.56‰ of the mass of the NdFeB magnetic powder. The liquid modifier has both lubricity and antioxidant properties.

[0107] The mixed magnetic powder was oriented, and the density of the compact after one-step orientation was 4.2 g / cm 3 Then the green compact is subjected to isostatic pressing to form a compact, followed by vacuum sintering. When the vacuum degree reaches 10 -2 Pa, sintering was started at 1065°C for 3 h, and the vacuum degree reached 10 -3 ~10 -4 Pa, and after the heat preservation is completed, the sintered magnet A is obtained by blast cooling to room temperature. The sintered magnet A is subjected to the first-level aging treatment at 920°C for 1 hour to obtain magnet B; the magnet B is subjected to the second-level aging treatment at 485°C for 3 hours, and after the heat preservation of the second-level aging treatment is completed, it is quickly cooled to room temperature to obtain a rare earth permanent magnet. The results of the magnet performance test are shown in Table 2.

[0108] Comparative Example 2

[0109] The same as Example 2 except for the following differences: In this comparative example, the solid modifier used when the NdFeB magnetic powder is formed in the jet milling stage is pure pentaerythritol stearate (PETS). The properties of the obtained rare earth permanent magnet are shown in Table 2.

[0110] Table 2

[0111] serial number Br / kGs HkDJ <![CDATA[BH max / MGOe]]> Hk / Hcj / % Example 2 14.64 15.7 53.15 99.7 Comparative Example 2 14.42 14.6 49.45 99.4

[0112] Preparation Example 3-Preparation of NdFeB Magnetic Powder

[0113] NdFeB magnetic powder is prepared according to the following components: PrNd 30.0wt%, Cu 0.13wt%, Co 0.4wt%, Al0.5wt%, Ga 0.2wt%, Zr 0.23wt%, B 0.91wt%, Fe balance. The raw materials containing the above components are vacuum smelted to obtain alloy strip pieces, and the alloy strip pieces are hydrogen crushed to obtain alloy coarse powder with a particle size range of 45 to 325μm.

[0114] The solid modifier is added to the alloy coarse powder and mixed, and then the mixture is subjected to jet milling to obtain NdFeB magnetic powder. The solid modifier is composed of: stearic acid amide (C 18 H 37NO) is 68.5wt%, and pentaerythritol stearate (PETS) is 31.5wt%. The addition amount of the above solid modifier is 0.4‰ of the mass of the alloy coarse powder.

[0115] The repose angle of the obtained NdFeB magnetic powder is 43.2°, the average specific surface diameter is 3.25μm, and D 90 / D 10 is 4.5, and the bulk density is 1.75g / cm 3 , tap density is 3.84g / cm 3 .

[0116] Example 3 - Preparation of rare earth permanent magnets

[0117] After adding a liquid modifier to the NdFeB magnetic powder obtained in Preparation Example 3, a high-efficiency shear mixer was used for shear mixing for 30 minutes to obtain a mixed magnetic powder. The liquid modifier is a mixture of methyl palmitate and tributyl borate mixed in equal volumes at a ratio of 1:1, and the amount of the liquid modifier added is 0.53‰ of the mass of the NdFeB magnetic powder. The liquid modifier has both lubricity and antioxidant properties.

[0118] The mixed magnetic powder was oriented, and the density of the compact after one-step orientation was 4.32 g / cm 3 Then the green compact is subjected to isostatic pressing to form a compact, followed by vacuum sintering. When the vacuum degree reaches 10 -2 Pa, sintering was started at 1068°C for 3 h, and the vacuum degree reached 10 -3 ~10 -4 Pa, and after the heat preservation, the sintered magnet A was obtained by blast cooling to room temperature. The sintered magnet A was subjected to the first aging treatment at 925°C for 0.5h to obtain magnet B; the magnet B was subjected to the second aging treatment at 496°C for 3h, and after the heat preservation of the second aging treatment, it was quickly cooled to room temperature to obtain a rare earth permanent magnet. The results of the magnet performance test are shown in Table 3.

[0119] Comparative Example 3

[0120] The same as Example 3 except for the following differences: In this comparative example, the solid modifier used when the NdFeB magnetic powder is formed in the jet mill stage is a simple stearic acid amide (C 18 H 37 NO). The properties of the obtained rare earth permanent magnets are shown in Table 3.

[0121] Table 3

[0122] serial number Br / kGs HkDJ <![CDATA[BH max / MGOe]]> Hk / Hcj / % Example 3 14.77 15.46 53.41 99.9 Comparative Example 3 14.45 14.67 49.84 99.3

[0123] Preparation Example 4-Preparation of NdFeB Magnetic Powder

[0124] NdFeB magnetic powder is prepared according to the following components: PrNd 30.0wt%, Cu 0.13wt%, Co 0.4wt%, Al0.5wt%, Ga 0.2wt%, Zr 0.23wt%, B 0.91wt%, Fe balance. The raw materials containing the above components are vacuum smelted to obtain alloy strip pieces, and the alloy strip pieces are hydrogen crushed to obtain alloy coarse powder with a particle size range of 45 to 325μm.

[0125] The solid modifier is added to the alloy coarse powder and mixed, and then the mixture is subjected to jet milling to obtain NdFeB magnetic powder. The solid modifier is composed of: stearic acid amide (C 18 H 37 NO) is 75wt%, and pentaerythritol stearate (PETS) is 25wt%. The addition amount of the above solid modifier is 0.52‰ of the mass of the alloy coarse powder.

[0126] The repose angle of the obtained NdFeB magnetic powder is 43.1°, the average specific surface diameter is 2.97μm, and D 90 / D 10 The bulk density is 4.26 and the apparent density is 1.84g / cm 3 , tap density is 3.85g / cm 3 .

[0127] Example 4 - Preparation of rare earth permanent magnets

[0128] After adding a liquid modifier to the NdFeB magnetic powder obtained in Preparation Example 4, a high-efficiency shear mixer was used for shear mixing for 30 minutes to obtain a mixed magnetic powder. The liquid modifier is a mixture of methyl laurate and triethyl borate mixed in equal volumes at a ratio of 1:1, and the amount of the liquid modifier added is 0.40‰ of the mass of the NdFeB magnetic powder. The liquid modifier has both lubricity and antioxidant properties.

[0129] The mixed magnetic powder was oriented, and the density of the compact after one-step orientation was 4.3 g / cm 3 Then the green compact is subjected to isostatic pressing to form a compact, followed by vacuum sintering. When the vacuum degree reaches 10 -2 Sintering started at 1070°C for 3 h, and the vacuum degree reached 10 -3 ~10 -4 Pa, after the heat preservation is completed, the sintered magnet A is obtained by blast cooling to room temperature. The sintered magnet A is subjected to the first-level aging treatment at 910°C for 2 hours to obtain magnet B; the magnet B is subjected to the second-level aging treatment at 500°C for 3 hours, and after the heat preservation of the second-level aging treatment is completed, it is quickly cooled to room temperature to obtain a rare earth permanent magnet. The results of the magnet performance test are shown in Table 4.

[0130] Comparative Example 4

[0131] The same as Example 4 except for the following differences: In this comparative example, the solid modifier used when the NdFeB magnetic powder is formed in the jet milling stage is ethylene bis stearamide. The properties of the obtained rare earth permanent magnet are shown in Table 4.

[0132] Table 4

[0133] serial number Br / kGs HkDJ <![CDATA[BH max / MGOe]]> Hk / Hcj / % Example 4 14.82 14.75 53.58 99.8 Comparative Example 4 14.48 14.82 49.46 99.5

[0134] In summary, the present invention is beneficial to reduce the repose angle of the obtained NdFeB magnetic powder by adding a specific solid modifier in the airflow milling process, that is, the fluidity of the NdFeB magnetic powder can be improved. The method of the present invention can further improve the remanence without substantially reducing the coercive force, and the magnetic energy product of the rare earth permanent magnet obtained by the method of the present invention is significantly improved. In addition, the squareness of the rare earth permanent magnet obtained by the present invention is improved.

[0135] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.

Claims

1. A method for improving the fluidity of NdFeB magnetic powder, characterized in that: The following steps are involved: 1) Providing alloy coarse powder obtained by hydrogen crushing of alloy strip pieces; 2) mixing the solid modifier with the alloy coarse powder obtained in step 1) and jet milling to obtain NdFeB magnetic powder; Wherein, the mass of the solid modifier is 0.2-0.8wt‰ of the mass of the alloy coarse powder; Wherein, the solid modifier is composed of an amide substance and pentaerythritol stearate, the mass of the amide substance accounts for 68-95wt% of the mass of the solid modifier; the amide substance is selected from stearic acid amide and / or oleic acid amide; The repose angle of the obtained NdFeB magnetic powder is less than or equal to 44.5°.

2. The method according to claim 1, characterized in that The amide substance is stearic acid amide.

3. A neodymium iron boron magnetic powder, characterized in that: It is prepared according to the method of claim 1 or 2.

4. A method for preparing a rare earth permanent magnet, characterized in that: The following steps are involved: (1) mixing the liquid modifier with the NdFeB magnetic powder according to claim 3 using a mixer to obtain mixed magnetic powder; (2) pressing the mixed magnetic powder into a shape, and then sintering and aging the mixture to obtain the rare earth permanent magnet; The liquid modifier comprises a high-level unsaturated fatty acid ester and an organic boron compound in a volume ratio of 1 to 4:1; the mass of the liquid modifier is 0.3 to 0.7 wt‰ of the mass of the NdFeB magnetic powder.

5. The preparation method according to claim 4, characterized in that: The liquid modifier is formed by a higher unsaturated fatty acid ester and an organic boron compound in a volume ratio of 1 to 4:

1.

6. The preparation method according to claim 4, characterized in that: The higher unsaturated fatty acid ester is selected from at least one of ethyl oleate, isooctyl oleate, methyl palmitate, methyl myristic acid, methyl stearate and methyl laurate; the organic boron compound is selected from at least one of triisopropyl borate, tributyl borate and triethyl borate.

7. The preparation method according to claim 4, characterized in that: When the vacuum degree is less than or equal to 1.0×10 -1 The green body obtained by pressing and forming is sintered at 1030-1155°C for 3-7h to obtain a sintered magnet A.

8. The preparation method according to claim 7, characterized in that: The aging treatment comprises keeping the sintered magnet A at 870-950° C. for 0.5-5 hours to obtain the magnet B; and keeping the magnet B at 400-650° C. for 1-5 hours to obtain the rare earth permanent magnet.

9. A rare earth permanent magnet, characterized in that: It is prepared according to the preparation method according to any one of claims 4 to 8.

10. Use of a solid modifier in improving the remanence of a rare earth permanent magnet, characterized in that: The solid modifier is composed of an amide substance and pentaerythritol stearate, wherein the amide substance accounts for 68-95wt% of the solid modifier; the amide substance is selected from stearic acid amide and / or oleic acid amide; and the method comprises the following steps: 1) Providing alloy coarse powder obtained by hydrogen crushing of alloy strip pieces; 2) mixing the solid modifier with the alloy coarse powder obtained in step 1) and jet milling to obtain NdFeB magnetic powder; Wherein, the mass of the solid modifier is 0.2 to 0.8 wt‰ of the mass of the alloy coarse powder.

Citation Information

Patent Citations

  • Antioxidant composition, rare earth permanent magnet, sintered magnet material and preparation method

    CN114220622A

  • Method for modifying high-fluidity sintered neodymium iron boron magnetic powder and neodymium iron boron sintered body

    CN115331941A

  • Preparation method of neodymium-iron-boron magnet

    CN115691924A